READINESS OF A FUTURE TEACHER FOR SELF-EDUCATION - S. N. Khatuntseva (Science and Innovation Center Publishing House, 2014)
Purpose. Тhe aim of this paper is to study the nature of teachers’ readiness to self-education as a component of self-improvement. Methodology. This paper examines the current state of scientific and theoretical study of the problem of the future teacher’s readiness for self-education. Results. The analysis of scientific and theoretical foundation of the problem of teacher’s readiness for self-education has been made. The essence of future teacher’s readiness for self-education as a component of self-improvement has been studied. It has been determined that readiness is a compound, dynamic formation of future teacher’s personality and it is the result of his training on the basis of theoretical knowledge about the nature, structure and content of self-education and practical skills and personal qualities. Motivational, cognitive, operational, active, personal, analytical and reflective components are the components of future teacher’s readiness for self-education as a part of self-improvement. Practical implications. Higher еducation, lifelong learning.